Midnight wolf - Ashley, Jennifer (Ashley, Jennifer. Shifters unbound novel., 2018)
Angus Murray, bouncer for a New Orleans Shifter bar, is sent to round up an elusive, Collar-less Shifter woman, Tamsin Calloway, who is causing trouble for Shifter Bureau, and possesses information they want. If Angus refuses, he risks losing his cub. He finds Tamsin but she's slippery and not about to be rounded up quietly. In fact, quiet is nothing Tamsin will ever be. She leads Angus on a wild chase, but he's determined to bring her in to save his son. Can Tamsin convince Angus she's worth helping before she's locked away by Shifter Bureau, Collared, or perhaps killed?